Epidemics, Psycho-Actives and Evangelical Conversion among the Airo-Pai of Amazonian Peru - Belaúnde, Luisa Elvira (Journal of contemporary religion, 2000)
The examination of Airo-Pai cultural dynamics and narratives of conversion reveals the indigenous interpretation of evangelicalism within the context of land colonisation by non-indigenous Nationals, coca farming and epidemics of diseases. The rejection of drugs and alcohol required of evangelicals is perceived by the indigenous population as instrumental in eradicating substance abuse and violence arising from colonisation. At the same time, the motivation for conversion derives from culturally specific understandings of the moral causes of illness and death and the ambivalent value of psycho-active substances and shamans. Evangelicalism provides a means of conceiving the overcoming of death and asserting an ancestral paradigm of sociality encapsulated in the notion of 'living well'.